A strategy for preparing spirobichroman dianhydride from bisphenol A and its resulting polyimide with low dielectric characteristic. Issue 2 (4th January 2017) - Tang, I Chun; Wang, Meng Wei; Wu, Chien Hsin; Dai, Shenghong A.; Jeng, Ru Jong; Lin, Ching Hsuan
Abstract : The high performance polyimide, SBC-DDM, exhibits a large free volume, leading to outstanding organo-solubility and a low dielectric constant. Abstract : A spirobichroman dianhydride (SBCDA ) was prepared through oxidation of an octamethyl spirobichroman (OMSBC ), which was synthesized from acid-fragmentation of bisphenol A by 3, 4-dimethylphenol, followed by Diels–Alder reaction. The reaction mechanism was proposed, and the optimal reaction conditions were discussed. Based on a high temperature solution polymerization ofSBCDA and 4, 4′-diaminodiphenylmethane (DDM), a spirobichroman-containing polyimide, SBC-DDM, was successfully prepared. Because of the contorted spiro-structure and rigid polymer backbone, SBC-DDM exhibits a large free volume, leading to outstanding organo-solubility and a low dielectric constant. In addition, the resulting film ofSBC-DDM shows foldability, a high glass transition temperature, and good thermal stability.